The role of Plzf in spermatogonial stem cell maintenance and differentiation: mapping the transcriptional dynamics and key interactions - Ghasemi, Nima; Azizi, Hossein; Razavi-Amoli, Seyedeh-Kiana; Skutella, Thomas (Cells, 2024)
Spermatogonial stem cells (SSCs) sustain and modulate spermatogenesis through intricate signaling pathways and transcription factors. Promyelocytic leukemia zinc-finger (Plzf, also known as Zbtb16) has been identified as a critical transcription factor influencing various signaling and differentiation pathways. Plzf plays a pivotal role in regulating the differentiation properties of SSCs and is essential for the proper maintenance of spermatogenesis. However, the transcription patterns of Plzf along the seminiferous tubules and its interaction network with adjacent partners still need to be fully elucidated. This study employed immunostaining techniques coupled with Fluidigm quantitative real-time polymerase chain reaction (Fluidigm qPCR) to quantify Plzf expression in undifferentiated and differentiated spermatogonia. Furthermore, we utilized bioinformatics analyses to identify Plzf partners and their associations with other regulatory factors. Immunohistostaining (IMH) revealed a high expression of Plzf in cells near the basal membrane of seminiferous tubules and a lower expression in the middle regions in vivo. Immunocytochemistry (ICC) demonstrated that undifferentiated spermatogonia exhibited significant Plzf positivity, whereas differentiated spermatogonia showed reduced Plzf expression in vitro. Fluidigm qPCR confirmed a significant differential expression of Plzf between undifferentiated and differentiated spermatogonia. In silico differential expression analysis between undifferentiated spermatogonia and spermatids indicated that Plzf is closely associated with Mycn, Lin28a, Kras, Ccnd1, and Jak1, highlighting the importance of these partnerships during spermatogenesis. Our findings suggest that the network of Plzf-related partners and their associated proteins involves differentiation, localization, apoptosis, and signal transduction. This comprehensive approach advances our understanding of Plzf transcription patterns and sheds light on its interactions with other cellular factors, revealing previously obscure pathways and interactions. These insights could lead to more effective diagnostic strategies for reproductive system-related diseases and inform the development of improved therapeutic and clinical applications.
Gesehen am 12.03.2025